Biomass Properties for Mechanization of Conditioning Processes (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
Substitution of fossil feedstock for energy and raw materials by biomass is important measure for GHG emission mitigation. Development of energy crop production and agricultural residue utilisation for energy are important goals of the rural policy. As chemical fertiliser production and usage corresponds to the consumption of oil fuel, biomass usage directly for energy production or as fertiliser are activities with equal importance. The main rural resources for biomass eco-technologies in Latvia are cereal straw residues, energy crops, emergent vegetation and peat from wetlands and sediments from lakes. Wide range of biomass properties cause necessity of appropriate mechanization equipment for biomass conditioning accordingly collection, conversion and usage technologies. The ecosystem approach means taking into account the interrelationships among land, air water and all living organisms including humans for mechanization equipment design of biomass technologies. Complex mechanisation of biomass technologies is based on implementation of ecosystem approach and investigation of properties of biomass in conditioning processes. For solid biofuel production densification properties of chopped stalk materials with different additives (peat, rapeseed cake) had been determined.